Problems related to voiding pattern in patients with hypospadias repair: i?s the problem related to only operation? - Baltrak, Yusuf Atakan; Karaman, Ibrahim; Karaman, Ayşe (Indian Journal of Child Health, 2018)
Background: Problems related to the urine flow are rather common in hypospadias patients. As these problems are detected during follow-up of urine flow in the post-operative period, it is difficult to determine whether it is a problem emerging secondary to the surgery or it is a congenital condition. Objective: The objective of this study was to evaluate the lower urinary tract functions in hypospadias patients with pre-operative and post-operative uroflowmetric examinations and to determine whether it is a complication of the surgery or a congenital condition. Materials and Methods: A total of 63 patients who underwent hypospadias surgery and were monitored postoperatively between January 2012 and January 2013 were enrolled in the study. Data about the pre- and post-operative uroflowmetry parameters were collected and compared. Results: Of total 83 patients, only 63 (76.8%) patients, whose parent’s provided the written consent, were studied. The mean age was 6.9±2.4 years (3–14 years). The mean bladder volume estimated according to the age of the patients was 266.5±71.7 ml. The mean bladder volume before and after the surgery was 179±56 ml and 189±53 ml, respectively, and the bladder volumes were 67% and 71% of the estimated bladder volume, respectively. There was no significant difference between the bladder volumes measured before and after the surgery (p=0.159). Furthermore, no significant change in the measurements regarding the maximum flow rate, time to maximum flow rate, total time of the urine flow, mean flow rate, voided volume, voiding time, and post-void residual volume was observed. Conclusion: The uroflowmetry is an easy-to-use, non-invasive, and objective method, which can be used for the early diagnosis of the urethral stricture following the hypospadias surgery and the evaluation of the obstructions in the lower urinary tract